Proyecciones de la buena fe en el Derecho Tributario: una mirada desde la jurisprudencia uruguaya - Bergstein, Jonás (2019)
Although the Bona Fides principle may appear to be an ambiguous or inconclusive definition at first instance, examination of its correct applicability is considerably relevant when determining a standard of conduct for taxpayers. Indeed, it is peaceful to recognise the transversality the Bona Fides has among all fields of the legal system. However, the question of its integrated realisation in tax law remains unresolved. In this paper, the author recommends some categories to analyse the values that inspire the principle in practice. To achieve this, the settled case law of the Uruguayan Administrative Dispute Tribunal (TCA in Spanish) is accurately revised and compared with legal literature to attain some carefully thought-out conclusions.